28-mer fragment derived from enterocin CRL35 displays an unexpected bactericidal effect on listeria cells - Masias, Emilse; Sanches, Paulo R.S. [UNESP]; Dupuy, Fernando G.; Acuña, Leonardo; Bellomio, Augusto; Cilli, Eduardo [UNESP]; Saavedra, Lucila; Minahk, Carlos (Bentham Science Publ Ltd, 2015)
Two shorter peptides derived from enterocin CRL35, a 43-mer bacteriocin, were synthesized i. e. the N-terminal fragment spanning from residues 1 to 15, and a 28-mer fragment that represents the Cterminal of enterocin CRL35, the residues 16 to 43. The separate peptides showed no activity when combined. On one hand, the 28-mer peptide displayed an unpredicted antimicrobial activity. On the other, 15mer peptide had no consistent anti-Listeria effect. The dissociation constants calculated from experimental data indicated that all peptides could bind at similar extent to the sensitive cells. However, transmembrane electrical potential was not dissipated to the same level by the different peptides; whereas the full-length and the C-terminal 28-mer fragment induced almost full dissipation, 15-mer fragment produced only a slow and incomplete effect. Furthermore, a different interaction of each peptide with membranes was demonstrated based on studies carried out with liposomes, which led us to conclude that activity was related to structure rather than to net positive charges. These results open up the possibility of designing new peptides based on the 28-mer fragment with enhanced activity, which would represent a promising approach for combating Listeria and other pathogens.
Keywords: Bacteriocins; Enterocin CRL35; Listeria; Synthetic peptides